Override ship maneuvering simulator using AR toolkit. Issue 1 (2nd January 2017) - Okazaki, Tadatsugi; Takaseki, Rei
Abstract: This paper proposes an override ship maneuvering simulator using an actual training ship for young pilot trainees. In this new simulator, augmented reality toolkit was used to reproduce scenery from the bridge of a large vessel on the actual training ship. Moreover, the system reproduced the large vessel's maneuverability under wind disturbance on the training ship. The effectiveness of the developed system was indicated with results of an actual ship experiment.